2016
DOI: 10.1148/radiol.2016151946
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield and Clinical Utility of Abdominopelvic CT Following Emergent Laparotomy for Trauma

Abstract: Purpose To determine the incidence of unexpected injuries that are diagnosed with computed tomography (CT) after emergent exploratory laparotomy for trauma and whether identification of such injuries results in additional surgery or angiography. Materials and Methods This HIPAA-compliant retrospective study was approved by the institutional review board, and the requirement for informed consent was waived. The trauma databases of two urban level 1 trauma centers were queried over a period of more than 5 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 18 publications
2
25
1
Order By: Relevance
“…Thus, postlaparotomy CT scan is a valuable adjunct to emergency surgery in trauma setting, often depicting unexpected injuries, besides confirming the presence of suspected injuries that were not fully explored at initial surgery. 8 The decision of whether to use open surgical technique or endovascular repair is based on what the surgeon believes is best in that particular scenario. Conventionally, open repair was used in the past for almost all iliac artery aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, postlaparotomy CT scan is a valuable adjunct to emergency surgery in trauma setting, often depicting unexpected injuries, besides confirming the presence of suspected injuries that were not fully explored at initial surgery. 8 The decision of whether to use open surgical technique or endovascular repair is based on what the surgeon believes is best in that particular scenario. Conventionally, open repair was used in the past for almost all iliac artery aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with abdominal trauma who are hemodynamically stable, CT with intravenous contrast material is the imaging modality of choice (17), but the optimal use of imaging in patients undergoing DCS without preoperative imaging is an area of continued study (18)(19)(20)(21)(22)(23). A CT examination performed in the early perioperative period may allow identification of injuries that require additional intervention or occult injuries in or beyond the surgical field and may provide the potential to change the patient treatment plan.…”
Section: Imaging After Dcsmentioning
confidence: 99%
“…A CT examination performed in the early perioperative period may allow identification of injuries that require additional intervention or occult injuries in or beyond the surgical field and may provide the potential to change the patient treatment plan. Recent studies have shown that approximately 10%-30% of patients who undergo DCS undergo CT within 48 hours of surgery (19,(21)(22)(23).…”
Section: Imaging After Dcsmentioning
confidence: 99%
See 2 more Smart Citations